2018
DOI: 10.1093/jac/dky317
|View full text |Cite|
|
Sign up to set email alerts
|

Stability and low induction propensity of cefiderocol against chromosomal AmpC β-lactamases of Pseudomonas aeruginosa and Enterobacter cloacae

Abstract: ObjectivesThe siderophore cephalosporin cefiderocol possesses in vitro activity against MDR Gram-negative bacteria. The stability of cefiderocol against serine- and metallo-type carbapenemases has been reported previously, but little is known about how cefiderocol interacts with chromosomal AmpC β-lactamases. We investigated a number of features of cefiderocol, namely antibacterial activity against AmpC overproducers, stability against AmpC β-lactamases and propensity for AmpC induction using Pseudomonas aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 15 publications
0
51
0
1
Order By: Relevance
“…Cefiderocol acts by binding to ferric iron, which enables it to use bacterial iron transporters to penetrate the external bacterial membrane. It also has high stability against ␤-lactamases, including serine-dependent ␤-lactamases and MBLs (317,318). The ability of cefiderocol to neutralize AmpC overproduction, its stability against these enzymes, and its ability to induce AmpC in Enterobacter cloacae and P. aeruginosa have been studied (318).…”
Section: Cefiderocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Cefiderocol acts by binding to ferric iron, which enables it to use bacterial iron transporters to penetrate the external bacterial membrane. It also has high stability against ␤-lactamases, including serine-dependent ␤-lactamases and MBLs (317,318). The ability of cefiderocol to neutralize AmpC overproduction, its stability against these enzymes, and its ability to induce AmpC in Enterobacter cloacae and P. aeruginosa have been studied (318).…”
Section: Cefiderocolmentioning
confidence: 99%
“…It also has high stability against ␤-lactamases, including serine-dependent ␤-lactamases and MBLs (317,318). The ability of cefiderocol to neutralize AmpC overproduction, its stability against these enzymes, and its ability to induce AmpC in Enterobacter cloacae and P. aeruginosa have been studied (318). While the MICs of ceftazidime and cefepime for the P. aeruginosa PAO1 strain increased 4-to 16-fold due to the inactivation of AmpD and DacB, cefiderocol MICs were only slightly affected.…”
Section: Cefiderocolmentioning
confidence: 99%
“…In addition to its broad range of antimicrobial activity, the stability of cefiderocol against β-lactamases, including ESBL, KPC, and NDM-1, has been confirmed. [78][79][80] Cefiderocol has been evaluated in phase III clinical trials 81) and was submitted in a New Drug Application to the FDA in December 2018 and in a Marketing Authorization Application to the European Medicines Agency in March 2019.…”
Section: Novel β-Lactams For Mdr Gram-negative Bacteriamentioning
confidence: 99%
“…In E. cloacae, enzyme affinities were [ 940-and [ 8fold lower for cefiderocol than for ceftazidime and cefepime, respectively. Double disc diffusion assays performed to detect the propensity for ampC induction of cefiderocol compared to imipenem demonstrated that cefiderocol did not induce ampC b-lactamases in P. aeruginosa or E. cloacae [19].…”
mentioning
confidence: 99%